An efficient synthesis of alpha-amino-delta-valerolactones by the Ugi five-center three-component reaction - Kim, YB; Park, SJ; Keum, G; Jang, MS; Kang, SB; Lee, DH; Kim, Y (WILEY-V C H VERLAG GMBH, 2002)
A novel approach to alpha-amino-delta-valerolactone derivatives 8 by the intramolecular Ugi five-center three-component reaction (U-5C-3CR) using the multifunctional starting material, L-pentahomoserine 5 is described.
Keywords: SOLUTION-PHASE SYNTHESIS; ARMSTRONGS CONVERTIBLE ISONITRILE; 4-COMPONENT CONDENSATION; MULTICOMPONENT REACTIONS; SOLID SUPPORT; LIBRARIES; ACIDS; ISOCYANIDES; PYRROLES; LACTAMS